2020
DOI: 10.3390/jcm10010035
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Overweight vs. Polycystic Ovary Syndrome: Disentangling Their Impact on Insulin Action in Pregnancy—A Prospective Study

Abstract: Background: To investigate insulin sensitivity and glucose metabolism in pregnant lean and overweight polycystic ovary syndrome (PCOS) patients vs. lean and overweight controls without PCOS. Methods: Prospective cohort study on 67 pregnant women (31 with PCOS and 36 controls, subdivided into overweight or obese and normal weight). All women underwent a 2h-OGTT including glucose, insulin, and C-peptide in early- and mid-gestation and were followed-up until delivery. Results: Insulin sensitivity and glucometabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…However, based on our analyses, this potential bias may determine inaccuracies in PREDIM calculation not exceeding 10-15%, which appears acceptable from a clinical point of view (details not shown). It is also worth noting that PREDIM provided reliable findings in some previous studies in pregnancy [56,102,107].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, based on our analyses, this potential bias may determine inaccuracies in PREDIM calculation not exceeding 10-15%, which appears acceptable from a clinical point of view (details not shown). It is also worth noting that PREDIM provided reliable findings in some previous studies in pregnancy [56,102,107].…”
Section: Discussionsupporting
confidence: 58%
“…In summary, we are not aware of any dataset with larger number of participants and all necessary features for the goals of the current study. On the other hand, the size of the current dataset is similar (slightly larger) to that analyzed in some of our previous studies related to pregnancy, where the glucose/insulin/C-peptide OGTT was available [ 56 , 100 102 ]. Of note, in one of those studies we already applied a technique classified within the machine learning domain (i.e., principal component analysis) [ 101 ].…”
Section: Discussionmentioning
confidence: 96%
“…Irregular menstrual patterns are a significant and independent risk factor for the development of GDM [10][11][12]. The most common risk factor identified across the majority of studies is a high BMI of over 25 kg/m2 [12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Risk Factors That Increase the Incidence And Prevalence Of G...mentioning
confidence: 99%
“…The current estimated prevalence of GDM in pregnant women with PCOS between studies was 26%, significantly higher than healthy controls [10,16,19,[21][22][23]26,27,35,38,40,41,44,47,[50][51][52][53][54][55]. However, several studies observed that there was no significant difference in the incidence or prevalence of GDM between pregnant women with and without PCOS [13,15,31,52,56]. When comparing whether or not women were amenorrheic or oligomenorrheic before pregnancy, there were conflicting results where one study found that the amenorrheic group was significantly more likely to develop GDM by 7.69%, while the other study found that oligomenorrhea was significantly associated with GDM concerning women with PCOS [12,14].…”
Section: Incidence Of Gestational Diabetes Mellitus In Polycystic Ova...mentioning
confidence: 99%